Psychoemotional disorders in men with infertility (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Infertile marriage is a problem on both the psychological and social spectrum in Uzbekistan, where starting a family is associated with procreation. Therefore, any problems in this area, the lack of a timely desired pregnancy lead to a state of chronic stress in the family, which is fraught with family conflicts, subsequently with the development of sexual dysfunctions, neurotic and somatic disorders (1,2,3).